If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-14+3x=3(8x+10)+x
We move all terms to the left:
-14+3x-(3(8x+10)+x)=0
We calculate terms in parentheses: -(3(8x+10)+x), so:We get rid of parentheses
3(8x+10)+x
We add all the numbers together, and all the variables
x+3(8x+10)
We multiply parentheses
x+24x+30
We add all the numbers together, and all the variables
25x+30
Back to the equation:
-(25x+30)
3x-25x-30-14=0
We add all the numbers together, and all the variables
-22x-44=0
We move all terms containing x to the left, all other terms to the right
-22x=44
x=44/-22
x=-2
| 2(x×2+4)=12 | | -3x+23.4=4.2 | | 5x+60-20x=-8-7 | | -2(3x-10)+8x=7x+20+7x | | 2(x•2+4)=12 | | 4b-4=6b+8 | | 5+u/8=-5.24 | | 11x+55^2=0 | | 2x+×/2=15 | | 2(x÷2+4)=12 | | -7v+5(v+6)=28 | | -12.2=5.3+w/7 | | 2-(x+5)-(x-2)=-3(x-3) | | 4+14=x+5 | | 5x-11=11x-33 | | 4y+6=(12.5)2.5 | | 2(x+2+4)=12 | | 18x+(-6)=8x+25 | | 11.6=4v-1.2 | | 45x+117=8x+450 | | 4x^2-12x+9=4 | | w^2+17w+66=w | | 6+9x+1=9x+7 | | x²-60x=13 | | 28=1/2(x+4)(x-6) | | 2(x/2+4)=12 | | 24-4)7-2t)=4(t-1) | | -8.7=-1.2+v/3 | | 41.6-6v=3.2 | | 8x+(-10)=5 | | 6/2g-1=3 | | 10v=2v+16 |